Education as a Catalyst for Socio-Economic Advancement in labor market: A Case Study of Azerbaijan's Reform Initiatives - Xanım Quliyeva Hikmat qızı (Modern Scientific Method, 2024)
This thesis explores education's vital role in society, focusing on its function as a formal organization and its impact on human capital development. It discusses Azerbaijan's education reforms, addressing socio-cultural functions and challenges like vocational education reform and socio-economic disparities. Emphasizing legislative and strategic initiatives, it advocates aligning education with labor market needs and fostering human resource development to shape Azerbaijan's future in the 21st century.